Kinetics of CO2 Absorption in Novel Tertiary N-Methyl-4-Piperidinol Solvent. (November 2019) - Sema, Teerawat; Khuenkaew, Wachiramon; Sirirathomsud, Ornicha
Graphical abstract: Highlights: Experimental kinetics of CO2 absorption into the novel MPDL solvent (k2 and kov ) are firstly introduced. Reaction kinetics can be expressed and ranked as:   k 2, M P D L = 1.66 × 10 7 E x p - 3903.6 T and MEA > DEA > AMP > MPDL > MDEA. Density, viscosity, Henry's constant, and physical liquid phase mass transfer coefficient of aqueous MPDL solutions are presented and comprehensively discussed. Abstract: In the present work, the reaction kinetics of CO2 absorption into aqueous solutions of novel N-methyl-4-piperidinol (MPDL) was experimentally determined in a stirred cell reactor over a MPDL concentration range of 0.5-2.0 M and a temperature range of 303-333 K. Based on the pseudo-first order assumption, a drop of pressure technique was used to extract the reaction rate constant, in terms of overall reaction rate constant (kov ) and second-order reaction rate constant (k2, MPDL ), from the experimental absorption data. Additionally, the physical properties and mass transfer data (i.e., density, viscosity, Henry's constant, and liquid phase mass transfer coefficient) of aqueous MPDL solutions were experimentally measured and comprehensively discussed. In the present work, the experimental k2, MPDL is firstly introduced and can be expressed as: k 2, M P D L = 1.66 × 10 7 E x p - 3903.6 T . The results also show that the CO2 absorption kinetics of MPDL can be ranked as: MEA > DEA > AMP > MPDL > MDEA. Even though novel MPDL has faster kinetics than conventional MDEA, it possesses too slow absorption kinetics to be used as a single solvent. Thus, it should be promoted with a very reactive amine to improve the overall CO2 absorption performance.